The Chañares formation: A window to a Middle Triassic tetrapod community - Mancuso, Adriana Cecilia (2014)
The Chañares Formation is known worldwide for its diverse and well-preserved Ladinian non-marine tetrapod assemblage, including a wide variety of archosauriform reptiles (proterochampsids, early offshoots of the crocodilian line and dinosaurian precursors) and synapsids represented by dicynodonts and cynodonts. This tetrapod record offers an opportunity to evaluate, within a taphonomic context, the palaeoecology of this Middle Triassic fauna. The taphonomic analysis of the Chañares assemblage, under precise stratigraphical control, indicates that it is a good representation of the original faunal composition allowing us to address the palaeoecological interactions between its components. Mass estimations and morphology-based palaeobiological inferences of Chañares tetrapods are used to reconstruct the trophic structure of the community. Chañares tetrapod fauna was numerically dominated by middle-sized herbivorous and small faunivorous cynodonts, whereas middle-sized faunivorous cynodonts and large dicynodonts were less common. In contrast to the therapsids, which show a low species-richness and high abundance, the archosauriforms are less abundant, but are the most taxonomically diverse group. The large paracrocodylomorphs (estimated body masses between 350 and 500 kg) are identified as the top predators of the community, and the traversodontid cynodonts and dicynodonts (estimated body masses reaching approximately 43 and 360 kg, respectively) are indentified as the base herbivores of the trophic pyramid. We conclude that the worldwide faunal composition in the Ladinian reveals two continental assemblages: an eastern Laurasian assemblage dominated by temnospondyl amphibians; and a western Gondwanan assemblage dominated by therapsids but including a wide diversity of archosauriforms.